Eräitä näkökohtia perinnöllisten tekijäin vaikutuksesta nautakarjan hedelmällisyyteen - Vainikainen, Viljo (Agricultural and Food Science, 1946)
Considering the decisive importance of fecundity on the whole Finnish cattle-breeding industry, the author has tried in the following research, which still is in its first phases, to bring forth some points of view, with which the selection of animals to be bred together could be made still more effective. Material has sofar only been collected from the districts of south-western Finland and Kuopio agricultural associations. The former includes west-Finnish and Ayrshire cattle, the cattle of the Kuopio province agricultural association area, on the other hand, chiefly consisting east-Finnish home-breed. The number of born twins has been examined in the research, their effect on production of the cow and later fecundity. In addition to this overtime calvings of cows have been examined, and to what extent breeding selection regarding proliferation can be rendered more effective on basis of this. A cow with an interval of 15 months or more between two successive calvings has been considered overtime. The material has been collected from reports sent to the Cattle-Breeding Dept, of the Agricultural Experimentary Institution by agricultural associations. Only cows who during their life-time have been more than twice overtime, have been recorded as overtimes. Material regarding twinresearch in the east-Finnish cattle remains for the time being considerably small, but the results have in any cace been published in this connection. The research continues and is extended to include all Finland’s 22 agricultural associations. The most important results of research are explained in the following summary 1) Cows giving twins have totalled 1,97 % of the Ayrshire cattle, 1,69 % of the western-Finnisch cattle and 0,63 % of the east-Finnish cattle. The small number of twins, in comparison with other groups, in the east-Finnish cattle may possible be a results of poorer feeding conditions. Calculated on basis of a single calving and in the above mentioned order, the number of twins born has been 0,33 %, 0,28 % and 0,09 %. Cows giving birth to two pairs of twins have amounted to 18,6 % in the Ayrshire cattle, 16,2 % in the western-Finnish cattle and 14,7 % in the east-Finnish cattle calculated on basis of the total number of twins born. Cows giving three pairs of twins have totalled in the above order 3.0 %, 2,7 % and 1,1 %. Both the Ayrshire and western-Finnish breeds include one cow who has given birth to four pairs of twins. Cows of an age higher than 10 years, which according to calculations made by the author is the average age of a Finnish cow, giving twins have totalled in the Ayrshire cattle 15,9 % of all Ayrshire cows giving twins, and correspondingly in the western-Finnish breed 19,6 % and in the east-Finnish breedc 25,7 %. 2) Twins including both sexes total about 50 % in the various breeds, and twins with only male or female calves about 25 % each. 3) Dead-born and back-to-life brought twin-individuals calculated from the total number of twins number in the above mentioned order in Ayrshire cattle 9.7 % and 11,5 %, in western-Finnish cattle 13,1 % and 8,7 % and in the east-Finnish cattle 10,5 % and 9,6 %. The birth of death-born female calves has been the smallest, and greatest among twins including both sexes. Female-calf twins have also included the greatest number of back-to-life brought calves. It is also worth observing that in some cases the female calf of a pair of twins including both sexes, has been brought to life, although it generally when mature remains infertile. 4) The differences in numbers of twins born during various months have been considerably small, but it seems, however, that both the Ayrshire and western-Finnish breeds generally give birth to more twins in the autumn and in March—April. With the east-Finnish breed March-—April months have also proven very succesful regarding twins. All examined breeds have included the greatest number of dead-born twins during July—August. 5) The production of milk and fats reached during the year of birth of twins, as also the fat-percentage in the milk, have been somewhat smaller than the corresponding productions during the year before and the year after. The mentioned differences however have no greater practical importance. 6) Cows twice or more overtimed included in those producing twins number in Ayrshire cattle 9,1 %, in western-Finnish cattle 2.7 % and in east-Finnish cattle 2,0 %, the corresponding percentages in the total cattles being 1,6 %, 0,7 % and 0.3 %. Of cows producing twins 13,2 % have become infertile in Ayrshire cattle, 13,3 % in western-Finnish cattle and 5,3 % in east-Finnish cattle, the average percentage of infertility in Finnish cattle being about 4-—5 %. The birth of twins thus severely overstrains the function of the cows sexual organs. 7) The daughters of twin-producing cows have despite their young age been more often overtime and infertile than the cows in the Finnish cattle to an average are. 8) Of cows who during their life-time have at least twice been overtime, 19,6 % in Ayrshire cattle have become infertile, the corresponding percentage in western-Finnish cattle being 24,5 % and in east-Finnish 12,8 %. 9) The daughters of overtime cows have become unregularly in calf or been infertile, some already after the first calving. 10) Of the 49 examined east-Finnish bulls, whose mothers and fathers mothers have been overtime or infertile, 24,8 % have produced cow-descendants which have been either weakly pregnant or infertile. 11) The mother or grandmothers from the fathers or mothers side, of the 17 east-Finnish bulls proved infertile, have either been overtime or later infertile. As a practical result of the above conclusions it can be established, that the birth of twins overstrains the sexual organs of the cow and can in many cases cause infertility. Inclination to giving twins in thus one of the factors decreasing fecundity, the effect of which is even felt in the daughters. In order to preserve regular pregnancy of cattle and to advance it, cows producing twins or even their descendants ought not to be chosen as pedigree animals or even as parents of bulls. In connection with examining of overtime births it has become evident, that cows twice or more overtime have later become infertile as also despite for the time being considerably small material it has become unquestionably evident, that both overtimedness and infertility are also dependant on hereditary factors. When developing permanent breeding cows and bulls the selection has thus to be directed to such mothers, who in addition to their other valuable characteristics have regularly become pregnant. As both overtimedness and inferiltity can be results of such outside factors, the elimination of which also causes the above drawbacks to disappear, it is possible, that in developing permanent breeding cows even mentioned modifications can be removed from breeding. For avoiding this naturally the fact whether infertility and overtimedness are caused by outside factors can to the extent possible be found out. According to my own opinion, however, only single overtimednesses may cause any reason for this, and especially if it is noticed in several cows in the same cattle. If, on the other hand, a second or further overtimednes or infertility is in question these individuals must be without mercy eliminated from the breeding-stock. Only a sharp breeding selection of this description can guarantee that all individuals with unadvantageous hereditary factors regarding fecundity, are eliminated from breeding. It is always practical to use inbreeding in various lines in turn in the cattle to guarantee results and establish the factors effecting fecundity naturally presupposing that the material is sufficient.